Expert Service-Oriented Architecture in C# 2005, Second Edition - Hasan, Jeffrey (Apress, 2012)
We software architects and developers live in a fascinating time. With the release of the .NET Framework in 2000, Web services technology has swept into our programming toolset and into our collective consciousness. Web services are the killer application for XML. Web services are the “new way” to call distributed objects remotely. Web services will take all of our integration headaches away and allow formerly incompatible systems to communicate again. What Microsoft developer has not recently thought to himself, “should I be building my application with Web services?” What .NET developer has not recently thought to himself, “I’m confused”? Every tidal wave has a genesis, and a momentum, and a final destination where it typically crashes head-on into a stable landmass and causes havoc and confusion. Web services technology is a tidal wave. The genesis is Microsoft’s strategic decision to simplify SOAP-based Web services development using a seamless set of integrated classes in the .NET Framework. The momentum is provided by a relentless marketing machine that promotes Web services as the solution for many of our worst IT problems. One destination is us, the architects and the developers who must understand this technology and learn how to implement it. Another destination is the manager, who must make strategic decisions on how to put this technology to its best use. The Web services technology tidal wave has created confusion for .NET developers because, quite simply, we do not know the best way to use it. We are wrapped up in misconceptions about what the technology is for, and this affects our judgment in using it properly. We will spend the first chapter clarifying these misconceptions, but let me reveal one:2